2014
DOI: 10.1227/neu.0000000000000515
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Guided Needle Localization of the Saphenous Nerve for Removal of Neuroma in the Infrapatellar Branches

Abstract: Ultrasound is a widely accepted and commonly utilized imaging modality; however, in this report, ultrasound-guided needle localization was used to aid in the resection of neuromas of small, painful sensory nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…A recent study using Computer Assisted Surgical Anatomy Mapping (CASAM) showed that the course of the IPBSN is highly variable, with numerous small terminal branches covering almost the whole anteromedial aspect of the knee that cannot be revealed during USG examination [ 14 ]. This is an important factor to consider when addressing post-procedural complications, as painful neuromas have been known to develop in cases when non-visible terminal branches of the IPBSN get transected [ 11 ]. Various safe zones, places where the risk of finding IPBSN nerve fibres are minimal, have been proposed by some researchers [ 6 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study using Computer Assisted Surgical Anatomy Mapping (CASAM) showed that the course of the IPBSN is highly variable, with numerous small terminal branches covering almost the whole anteromedial aspect of the knee that cannot be revealed during USG examination [ 14 ]. This is an important factor to consider when addressing post-procedural complications, as painful neuromas have been known to develop in cases when non-visible terminal branches of the IPBSN get transected [ 11 ]. Various safe zones, places where the risk of finding IPBSN nerve fibres are minimal, have been proposed by some researchers [ 6 , 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical technique has been implicated in the sectioning of the saphenous nerve during medial parapatellar incision, portal placement, traction by medial retractors, proximity of the nerve branches to the gracilis tendon and knee joint, patient positioning, and anatomical variations in the course of the nerve branches. 17,49,[54][55][56]…”
Section: Iatrogenic Neuropathymentioning
confidence: 99%
“…1,4,7,11,20 Furthermore, several studies have confirmed the accuracy of ultrasonography in identifying peripheral nerves and its usefulness for guidance for the peripheral nerve surgeon. 5,10,12,13,16 The use of MB, also referred to as supravital staining in the literature, is a well-known technique in the field of anatomical study.…”
Section: Neurosurgical Focusmentioning
confidence: 99%
“…1,4,7,11,20 Furthermore, several studies have confirmed the accuracy of ultrasonography in identifying peripheral nerves and its usefulness for guidance for the peripheral nerve surgeon. 5,10,12,13,16 The use of MB, also referred to as supravital staining in the literature, is a well-known technique in the field of anatomical study.9 On the surgical frontier, MB has been incorporated into the operating room safely by surgeons of various specialties to improve identification of vital obJect The objective of this study was to provide a technique that could be used in the preoperative period to facilitate the surgical exploration of peripheral nerve pathology. methods The authors describe a technique in which 1) ultrasonography is used in the immediate preoperative period to identify target peripheral nerves, 2) an ultrasound-guided needle electrode is used to stimulate peripheral nerves to confirm their position, and then 3) a methylene blue (MB) injection is performed to mark the peripheral nerve pathology to facilitate surgical exploration.…”
mentioning
confidence: 99%